Impact of Consumption of Bananas on Attraction of Anopheles stephensi to Humans - Paskewitz, Susan; Irwin, Patrick; Konwinski, Nic; Larson, Scott (Insects (Basel, Switzerland), 2018)
Humans vary in attractiveness to mosquitoes, a phenomenon that is largely attributed to differences in physical cues such as heat and volatile odors emanating from breath and skin. Diet can change human odors but whether specific dietary components alter host attractiveness is largely unexplored. We identified bananas as a target for study following a survey of the internet for advice on avoiding mosquito bites. Human attractiveness to Anopheles stephensi Liston was measured using a glass vial bioassay where mosquito contacts were measured before and 1–3 h after ingestion of bananas or grapes. Consumption of grapes had no effect on the number of contacts but banana ingestion resulted in a significant increase in the overall number of contacts in spite of individual variation that included some subjects who showed no effect or decreases in contacts. Further tests with a single volunteer showed that the effect was repeatable and consistent across 15 trials. The magnitude of the increase was not affected by the number of bananas eaten. Increased contact counts after banana ingestion were also observed when A. gambiae Giles was tested. These results support the hypothesis that diet plays an important role in mediating host attractiveness to anopheline mosquitoes.